The rationale for recommending fixed-dose combination tablets for treatment of tuberculosis - Blomberg Bjørn; Spinaci Sergio; Fourie Bernard; Laing Richard (The World Health Organization, 2001)
There is considerable exigency to take all necessary steps to cure tuberculosis cases and prevent further emergence of drug-resistant tuberculosis. The most important of these steps is to ensure that the treatment, particularly of sputum smear-positive cases, is adequate and that patients adhere to their treatment by supervised, direct observation of drug-taking according to the standardized regimens. Use of fixed-dose combinations (FDCs) of tablets against tuberculosis is now being recommended by WHO and the International Union Against Tuberculosis and Lung Disease (IUATLD) as an additional step to ensuring proper treatment. FDCs simplify the prescription of drugs and the management of drug supply, and may also limit the risk of drug-resistant tuberculosis arising as a result of inappropriate drug selection and monotherapy. Only FDCs of proven quality and proven rifampicin bioavailability should be purchased and used. In most situations, blood levels of the drugs are inadequate because of poor drug quality rather than poor absorption. This is true irrespective of the human immunodeficiency virus (HIV) infection status of the tuberculosis patients (other than those with overt acquired immunodeficiency syndrome, with CD4 counts <200 cells/mm³). Currently, WHO, IUATLD and their partners are developing strategies for ensuring that only quality FDCs are used in tuberculosis programmes. A simplified and effective protocol for assessment of rifampicin bioavailability has been developed, and laboratories are being recruited to form a supranational network for quality assurance of FDCs. Standardization of FDC drug formulations has been proposed, which limits rifampicin-containing preparations to nine (including a four-drug FDC and three paediatric FDCs).